Forest Contribution to Climate Change Mitigation: Management Oriented to Carbon Capture and Storage - Nunes, Leonel; Meireles, Catarina; Pinto Gomes, Carlos; Almeida Ribeiro, Nuno (Climate, 2020)
Today, climate change is assumed by many researchers and scholars as a certainty and ispresented as the biggest challenge humanity has ever faced. It is commonly accepted that anthropogenicgreenhouse gas emissions are the main cause that is accelerating the process. Therefore, it is urgentto find solutions to mitigate climate change, mainly because the intense effects have already beenfelt, in many cases in the form of the occurrence of extremely violent weather events. Forests areundoubtedly one of the most effective and easiest ways to provide the function of carbon sinks.However, it is essential and convenient to analyze the permanence time of this carbon in forests,because this permanence time depends directly on the forest management model used. This articleaims to analyze forest management models from the perspective of carbon residence time in temperateforests, dividing the models into three types, namely carbon conservation models, carbon storagemodels, and carbon substitution models, according to their ability to contribute to functioning ascarbon sinks, thereby contributing to the mitigation of climate change.
Keywords: forest management; climate change; carbon sinks; carbon cycle